When microplastics/plastics meet metal-organic frameworks: turning threats into opportunities - Wu, Pengfei; Guo, Mengting; Zhang, Ran-Wei; Huang, Qing; Wang, Guibin; Lan, Ya-Qian (Chemical science (Cambridge), 2024)
Significant efforts have been devoted to removal and recycling of microplastics (MPs; <5 mm) to address the environmental crises caused by their ubiquitous presence and improper treatment. Metal-organic frameworks (MOFs) demonstrate compatibility with MPs/plastics through adsorption, degradation, or assembly with the MPs/plastic polymers. Above 90% of MPs/plastic particles can be adsorbed on MOF materials via the hydrophobic interaction, electrical attraction, π-π stacking, and van der Waals forces. Meanwhile, certain MOFs have successfully converted various types of plastics into high-valued small molecules through thermocatalysis and photocatalysis. In thermocatalysis, the primary process should be C-O bond cleavage, whereas in photocatalysis it ought to be the generation of reactive oxygen species (ROS). Moreover, the construction of novel MOFs using waste MPs/plastics as the ligands was mostly accomplished through three dominant ways, including glycolysis, hydrolysis and methanolysis. Once successfully composited, the MOF@plastic materials illustrated tremendous promise for interdisciplinary research in multifunctional applications, including sewage treatment, gas adsorption/separation, and the preparation of microbial fuel cells, plastic scintillators and other sensors. The review explicated the relationships between MPs/plastics and MOF materials, as well as the challenges and perspectives for their development. It can provide a deeper understanding of how MOFs remove/degrade MP/plastic particles, how MPs/plastics are recycled to prepare MOFs, and how to build multifunctional MOF@plastic composites. Overall, this analysis is anticipated to outline future prospects for turning the threats (MPs/plastics contamination) into opportunities ( e.g. , as ligands to prepare MOF or MOF@plastic materials for further applications). The study discussed how MOFs treat microplastics, how to make plastic-based MOFs, and how MOF@plastic composites can be used. It aids in understanding how to convert plastic/microplastic concerns into opportunities for high-valued products.